Peningkatan Hasil Belajar Pendidikan Agama Islam pada Materi Asmaul Husna melalui Metode Index Card Match pada Siswa Sekolah Dasar - Yeyen Mardanita; Kasmantoni Kasmantoni (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Low learning outcomes in Islamic Religious Education on the Asmaul Husna material indicate that the learning process has not actively engaged students, suggesting the need for a more interactive and enjoyable learning method. Objective: This study aimed to improve students’ learning outcomes in Islamic Religious Education on the Asmaul Husna material through the implementation of the Index Card Match method for fourth-grade students at SDN 08 Seluma, Talo Kecil District, Seluma Regency. Method: This study employed a qualitative approach using Classroom Action Research (CAR), conducted in two cycles comprising planning, implementation, observation, and reflection. Data were collected through tests, observations, and documentation. Result: The findings revealed that implementing the Index Card Match method improved students’ learning outcomes, participation, cooperation, and confidence during the learning process. Students became more active in finding matching cards, engaging in discussions, and presenting their learning results to the class. Conclusion: The study concludes that the Index Card Match method is effective in teaching Islamic Religious Education, particularly the Asmaul Husna material. Contribution: This study develops innovative and engaging active learning methods for elementary education.